JPEPA, a decade after: Evaluating the effects in Philippine exports using the Synthetic Control Method (SCM) - Mark Anthony A. Barral; Francis Mark A. Quimba (Philippine Institute for Development Studies (PIDS), 2019)
Free trade agreements (FTAs) and regional trade agreements (RTAs), as a national policy, have proliferated in the recent decades as countries perceived trade agreements to effectively reduce trade barriers, thus helping expand market access, protect local markets, and enhance efficiency and productivity of domestic industries. Such preferential trade agreements, however, can have advantages or disadvantages. The Japan-Philippines Economic Partnership Agreement, which is the first and only FTA of the Philippines, was entered into in order to facilitate and promote free trans-border flow of goods, services, capital, and people between the two countries. Whether it was able to deliver its intended benefits and what determined its success are two focal national interests. Evaluating such agreement can be done through detailed examinations of economic conditions before and after the implementation. This requires a comparison group whose outcomes can be contrasted with the outcome of the agreement to separate the effects that are attributable to this agreement from the effects of other factors. This, however, is a rigorous and difficult task and existing approaches fall short in providing sufficient measures. In order to understand the effects of JPEPA, particularly on Philippine exports, without being hampered by the limitations in existing approaches, this paper explores the use of Synthetic control method (SCM). The results generally reveal that Philippine exports benefited from the agreement as determined by the difference in the actual exports and the counterfactual exports. Investigating the effects at the sector-level, however, yield varying results.
Keywords: 330; Japan-Philippines Economic Cooperation; JPEPA; Synthetic Control Method; SCM; bilateral trade agreement; Free Trade Agreement; FTA; Trade in Goods